Acute Encephalitis Hospitalizations, California, 1990–1999: Unrecognized Arboviral Encephalitis? - Rosalie T. Trevejo (Emerging Infectious Diseases, 2004)
Historically, Western equine encephalomyelitis and St. Louis encephalitis caused substantial human and equine illness and death in California. This study describes the epidemiology of encephalitis with data from 13,807 patients hospitalized in California with acute encephalitis from 1990 through 1999. The incidence of encephalitis hospitalizations decreased over this period. The greatest proportion of case-patients was hospitalized in the winter. Encephalitis of unspecified origin was the most common diagnosis, and arboviral encephalitis was the least common. Some California counties had concurrent increases in encephalitis rates and in detected arboviral activity in sentinel chickens and mosquito vectors. However, a diagnosis of arboviral encephalitis was made for few hospitalized patients in these counties during these periods. Although some arboviral encephalitis cases may have been undiagnosed, such cases probably did not occur frequently. Active hospital-based surveillance during periods of heightened sylvatic arboviral activity could increase detection of arboviral encephalitis.